2018
DOI: 10.1002/berj.3327
|View full text |Cite
|
Sign up to set email alerts
|

Educational influences on young people's support for fundamental British values

Abstract: In 2014 the British government called on schools to actively promote fundamental British values (FBVs), seeing this as an effective way to prevent the radicalisation of young people. The government considers these values to include democracy, individual liberty, the rule of law and respect for people of different backgrounds and religions. Rather than criticising this policy on theoretical or ideological grounds, as many studies have done, the current article aims to ascertain support for the values labelled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Ultimately, given that students are already very likely to support the government's list of FBVs (Janmaat, ) and exceedingly unlikely to support political violence for any reason (Jerome & Elwick, ), our review of the research indicates that the Prevent duty may well be having a series of unnecessary and unintended effects, which are threatening long‐established policies tackling racism, promoting equalities and supporting community cohesion. There is evidence that teachers and school leaders may exercise their agency to challenge or minimise these negative side‐effects, but with approximately half a million teachers in England, it seems unlikely that we can rely on them all individually to respond to this challenge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, given that students are already very likely to support the government's list of FBVs (Janmaat, ) and exceedingly unlikely to support political violence for any reason (Jerome & Elwick, ), our review of the research indicates that the Prevent duty may well be having a series of unnecessary and unintended effects, which are threatening long‐established policies tackling racism, promoting equalities and supporting community cohesion. There is evidence that teachers and school leaders may exercise their agency to challenge or minimise these negative side‐effects, but with approximately half a million teachers in England, it seems unlikely that we can rely on them all individually to respond to this challenge.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, Janmaat's () research takes a rather different approach and reanalyses a longitudinal data set of 420 young people collected throughout their secondary education, until they were 22 years of age. He builds a measure of support for the FBVs by compiling items from an international civics survey.…”
Section: Theme 2: Britishnessmentioning
confidence: 99%
“…In addition Green (2017) conducted three focus groups with Muslim teenagers, which included some discussion of their experiences of school and college. We have also identified one relevant secondary study in which Janmaat (2018) re-analysed existing data from 420 young people for evidence of their knowledge of, and support for, the FBVs. Given that there are over 12 million people below the age of 18 in the UK, we cannot claim to provide a reliable overview of the situation for all children and young people, especially given the small research base on which we are able to draw.…”
Section: What Do Students Want To Learn?mentioning
confidence: 99%
“…Hoskins and Janmaat () found that in England, both the level and type of educational pathways pursued from the age of 14 have an independent correlation with reported voting and protesting at age 19–20. Janmaat () in fact finds that type of education matters more than level of education for several democratic and civic values for 23‐year‐olds in England. Finally, Geboers et al .…”
Section: Theoretical Frameworkmentioning
confidence: 99%